2015
DOI: 10.1186/s12906-015-0777-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Qing’e formula on the in vitro differentiation of bone marrow-derived mesenchymal stem cells from proximal femurs of postmenopausal osteoporotic mice

Abstract: BackgroundQing’e formula (QEF), prepared from an ancient Chinese recipe, was previously suggested to regulate bone metabolism and improve bone mineral density in patients with osteoporosis. To study the effects of medicated serum containing QEF on the in vitro differentiation of bone marrow-derived mesenchymal stem cells (BMSCs) isolated from the proximal femurs of postmenopausal osteoporosis (PMOP) mice.MethodsUsing an established mouse model of PMOP, mononuclear cells were isolated from the bone marrow prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…It is widely recognized that AR activating the neurotransmitter-based effects [2427], rather than the estrogen activity [28, 29], is an important mechanism for alleviating menopausal symptoms, such as hot flashes and night sweats. Numerous studies have also confirmed that AR does not have a stimulating effect on the levels of blood estrogen and progestin or estrogen target organs such as the uterus, ovaries, breast, and blood vessels [9, 22, 30]. However, studies on the effect of AR on the skeletal system revealed that AR promotes the secretion of OPG and OC by human osteoblasts, increases the OPG/RANKL ratio, and promotes the formation of mineralized nodules in MC3T3-E1 preosteoblasts, all of which could be blocked by ICI 182,780 [17, 18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is widely recognized that AR activating the neurotransmitter-based effects [2427], rather than the estrogen activity [28, 29], is an important mechanism for alleviating menopausal symptoms, such as hot flashes and night sweats. Numerous studies have also confirmed that AR does not have a stimulating effect on the levels of blood estrogen and progestin or estrogen target organs such as the uterus, ovaries, breast, and blood vessels [9, 22, 30]. However, studies on the effect of AR on the skeletal system revealed that AR promotes the secretion of OPG and OC by human osteoblasts, increases the OPG/RANKL ratio, and promotes the formation of mineralized nodules in MC3T3-E1 preosteoblasts, all of which could be blocked by ICI 182,780 [17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…A previously described method was applied for cell extraction and maintenance [22]. SD rats were euthanized and the thigh and shank bones were quickly isolated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, understanding the time and dose effects of ZGP on BMSC osteogenic differentiation will be clinically relevant in the treatment of OP. Although the effect of classic kidney-tonifying compounds on BMSC osteogenic differentiation is still poorly understood, a few preparations such as six-ingredient rehmannia pill, sexoton pill [ 71 , 72 ], Erxian decoction [ 73 ], and Qing'e pill [ 74 ] have been shown to promote osteogenic differentiation and inhibit angiogenic differentiation of BMSCs. Therefore, it is important to compare the effects of the different kidney-tonifying compounds on BMSC osteogenic differentiation vis-à-vis OP treatment.…”
Section: Future Directions?mentioning
confidence: 99%
“…However, the long-term use of estrogen increases the risk of breast cancer, endometrial cancer, cardiovascular accident and vascular embolism (19). In recent years, the prevention and treatment of PMOP by traditional Chinese medicine is attracting more and more attention (20,21). It is of great significance to find an estrogen replacement medicine for the prevention and treatment of postmenopausal osteoporosis in traditional medicine.…”
mentioning
confidence: 99%